Filantrocapitalismo y Cooperación al Desarrollo: el caso de la lucha contra la poliomielitis - Mediavilla-Merino, Juan José (Revista Iberoamericana de Estudios de Desarrollo)
The philanthropic activities of major foundations have made a significant importance in recent decades in International Development Cooperation. In a global economic perspective, philanthropic foundations work in areas that formerly belonged to the State. This loss of social policies by the State and the pursuit of a global strategy for development have promoted the growth of these organizations. Public-Private Partnerships for Development are, in most cases, the innovative way they choose for their funding, using the distribution of risks and benefits. We are witness of a form of philanthropy in which philanthropists are motivated not only a desire altruistic, but is seeking projects that are beneficial.